Deciphering the immobilization of lipases on hydrophobic wrinkled silica nanoparticles - Pota G.; Andres-Sanz D.; Gallego M.; Vitiello G.; Lopez-Gallego F.; Costantini A.; Califano V. (International Journal of Biological Macromolecules, 2024)
In this work, the adsorption of Candida antarctica B (CALB) and Rhizomucor miehei (RML) lipases into hydrophobic wrinkled silica nanoparticles (WSNs) is investigated. WSNs are hydrophobized by chemical vapor deposition. Both proteins are homogeneously distributed inside the pores of the nanoparticles, as confirmed by Transmission Electron Microscopy and Energy Dispersive X-ray measurements. The maximum enzyme load of CALB is twice that obtained for RML. Fourier Transform Infrared Spectroscopy confirms the preservation of the enzyme secondary structure after immobilization for both enzymes. Adsorption isotherms fit to a Langmuir model, resulting in a binding constant (KL) for RML 4.5-fold higher than that for CALB, indicating stronger binding for the former. Kinetic analysis reveals a positive correlation between enzyme load and RML activity unlike CALB where activity decreases along the enzyme load increases. Immobilization allows for enhancing the thermal stability of both lipases. Finally, CALB outperforms RML in the hydrolysis of ethyl-3-hydroxybutyrate. However, immobilized CALB yielded 20 % less 3-HBA than free lipase, while immobilized RML increases 3-fold the 3-HBA yield when compared with the free enzyme. The improved performance of immobilized RML can be explained due to the interfacial hyperactivation undergone by this lipase when immobilized on the superhydrophobic surface of WSNs.